Pematuhan dan Penyimpangan Prinsip Kesantunan Berbahasa dalam Wacana Buku Teks Bahasa Indonesia - Nur Nisai Muslihah; Riko Febrianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
The purpose of this study was to describe the form of compliance and deviation of the principle of language politeness as well as the level of language politeness in the textbooks were focused on Bahasa Indonesia textbook of SMA, MA, SMK, MAK Class 10 Curriculum 2013 Revised Edition 2016 by Suherli etc. The method used in this study was quantitative descriptive method by using reading and recording as data collecting technique. Data analysis was done by using matching method. The determination of the form of complience and deviation of the principles of language politeness refered to the theories of politeness and Leechs politeness principles. While the the level of politeness was calculated based on the tendency compliance and deviations on the principle of language politeness. The results showed that there were 211 speech either obey or deviate to the principle of politeness. The obedience amounted to 157 speech, consisting of 63 maxims of wisdom, 6 generosity maxims, 18 reward maxims, and 70 maxim of consensus. The deviation of the principle of language politeness had a lower proportion of 54 speech, consisting of 52 maxims of wisdom, and 2 maxims of appreciation. Level of discourse politics contained in textbooks Indonesian SMA, MA, SMK, MAK Class 10 Curriculum 2013 revised edition 2016. It can be seen from the compliance rate having 74.4 percent, percentage which is in the range of 61percent to 80 percent with the polite category, and the deviation has the percentage of 25.6 percent which is in the range of 21 percent to 40 percent with the polite category. Keywords: Compliance, Deviation, Modesty, Discourse, Textbook.